Nutrition and fish health (Food Products Press, 2001)
Diseases are a major threat to the sustainability of the aquaculture industry. Because antibiotics have many drawbacks, increasing importance is being placed on understanding the mechanisms that make nutrition a key factor in host defense against pathogens. Nutrition and Fish Health is the first book to provide comprehensive information on nutrition as a means to improve fish health and defend against infection.